Femorofemoral Crossover Bypass for Unilateral Iliac Artery Occlusive Disease or Secondary Aortoenetric Fistula - Kumar Jha, Anik; Pandeya, Prachi; Dhakal, Sudan; Raj Pandey, Sandeep (Annapurna Journal of Health Sciences, 2023)
Femorofemoral bypass is indicated in symptomatic lower-extremity ischemia due to acute or chronic occlusion of a unilateral Iliac Artery, adjunct to an endovascular unilateral Aortoiliac(AI) exclusion of an Abdominal Aortic Aneurysm (AAA), unavailability of endovascular options for management of iliac occlusive disease,etc.It’s contraindicated compromised inflow AI arterial segment, significant obesity that may cause unfavorable graft geometry ,etc. The complication of which leads to femoral nerve injury , hematoma, graft thrombosis and distal emboli etc. Here, We present several cases of Femorofemoral crossover bypass cases in this case study.